Hermann Kolbe: L’ultimo resistente - Noto, Renato (Chimica nella Scuola, 2024)
With the advent of the structural theory, modern organic chemistry began to develop. Some of the most famous chemists of the time took a cold attitude towards the new theory, others were decidedly against it. Prominent among them was Kolbe, who was decidedly hostile not only towards the structural theory but also towards those who were its greatest supporters.